2018
DOI: 10.3892/or.2018.6617
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing O-GlcNAcylation affects the malignant transformation of MCF-7 cells via Hsp27 expression and its O-GlcNAc modification

Abstract: O-GlcNAcylation is a dynamic posttranslational modification of nucleoplasmic proteins. Previously, we reported that the O-GlcNAcylation level was increased in primary breast and colorectal cancer tissues. However, its precise roles in cancer development and progression are still largely unexplored. The aim of the present study was to investigate the roles of O-GlcNAcylation in the malignant transformation of cancer cell lines. O-GlcNAcylation level was examined in six cancer cell lines including breast (MCF-7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Reducing NPM1 expression using siRNA resulted in a significant decrease in cell proliferation and induced cell cycle arrest in leukemia, colon and breast cancer (30)(31)(32). Moreover, the present study supports the results of previous studies which have demonstrated that O-GlcNAc regulates the cellular stress responses via the expression of numerous HSPs, including HSP27 (14,33). HSP27 expression levels affect cell proliferation, migration and invasion abilities in several types of cancer, such as liver, prostate and breast cancer (34)(35)(36).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Reducing NPM1 expression using siRNA resulted in a significant decrease in cell proliferation and induced cell cycle arrest in leukemia, colon and breast cancer (30)(31)(32). Moreover, the present study supports the results of previous studies which have demonstrated that O-GlcNAc regulates the cellular stress responses via the expression of numerous HSPs, including HSP27 (14,33). HSP27 expression levels affect cell proliferation, migration and invasion abilities in several types of cancer, such as liver, prostate and breast cancer (34)(35)(36).…”
Section: Discussionsupporting
confidence: 89%
“…OGT is essential for cell viability and OGT depletion results in embryonic lethality (20). Moreover, our previous study revealed that OGT knockdown caused a marked decrease in cell viability under the anoikis resistant conditions (14). Furthermore, OGT silencing reduces the migratory and invasive capacities in a number of different types of cancer including breast (21), prostate (22), ovarian (23) and colon cancer (24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations